Chromatographic fractionation of lithium isotope in aqueous solution using bifunctional ion-exchange resin. Issue 12 (12th August 2020) - Tachibana, Yu; Vidyadharan Nair, Vijay; Mohan, Sankaralingam; Suzuki, Tatsuya
ABSTRACT: We have examined the effect of bifunctional group in the same cross-linkage degree on the Li isotope fractionation in the cation exchange reaction in the aqueous solutions ranging in temperature from 278 to 333 K. For this purpose, the sulfonated pyridine-styrene-divinylbenzene resin with the cross-linkage degree of 50 wt%, embedded in porous silica beads was successfully synthesized by a typical polymerization method. The isotope separation coefficients ( ε ) per unit mass ( ε/ΔMass ) was 8.1 × 10 –4 at 298 K. Therefore, the effect of bifunctional group against the ε / ΔMass value has been discussed, compared with those of previous works.